The Introduction of Eichhornia Crassipes into the High Rate Algal Pond to Remove Nitrogen from Wastewater - Bich, Nguyen Ngoc (1998)
The treatment of wastewater using algal cultures has been researched and developed since 1950. The High Rate Algal Pond (HRAP) is the most efficient of this type of treatment, particularly for nitrogen removal. However, the main problem with the HRAP is the high level of organic suspended solids in the treated wastewater. Furthermore, nutrients released from the lysis of algal cells may give rise to eutrophication in the receiving water. A laboratory-scale experiment was carried out using the HRAP in the company of anaquatic plant, waterhyacinth Eichhornia crassipes, as an integrated system to remove nitrogen from wastewater. The dominant algal species used was Chlorella vulgaris. Twenty runs in t he bat ch mode were operated under the conventional HRAP and the HRAP - waterhyacinth combination system. Three runs were operated in the continuous mode using the HRAP - waterhyacinth system with 50% surface area coverage and 3 different retention times (3 days, 6 days, and 9 days). Comparison of the conventional HRAP and the HRAP waterhyacinth system for treating diluted raw wastewater from rubber latex concentrate processing revealed better nitrogen removal efficiency by the HRAP-waterhyacinth system. Total Kjeldahl Nitrogen in the treated wastewater was 23% lower in the HRAP with waterhyacinth than that in the normal HRAP. Significant reduction of suspended solids was also recorded. Total Suspended Solids of the effluent in the HRAP-waterhyacinth system was generally less than 50mg/L wherea sit was greater than 450mg/L in the conventional HRAP.